People with Disabilities, Self-Determination and Very Personal Acts - Di Martino, Gaetano (Teisė, 2020)
The evolution of medical, social and economic sciences and, more generally, the way of thinking has profoundly changed the relationship between Society and people with disabilities: these persons, from the recipients of social protection and care, have become an active part of Society. Therefore, this publication analyzes the basis and limits of the powers of persons with disabilities in the context of ethical, political, religious and legal values.
Keywords: protection; incapacitated; fundamental rights; evolution of law; very personal acts; choices about health treatments